Chlorate accumulation in commercial lettuce cultivated in open field and irrigated with reclaimed water. (August 2020) - Garrido, Yolanda; Marín, Alicia; Tudela, Juan A.; Truchado, Pilar; Allende, Ana; Gil, María I.
Abstract: The use of reclaimed water for irrigation after disinfection can provide significant environmental, social and economic benefits and solve the problem of water scarcity. The occurrence of disinfection by-products (DBPs) as pollutants in irrigation water has been highlighted as a health risk of emerging concern since they can be uptaken by the plant and accumulated in the edible parts during crop production. Little attention has been paid to the occurrence of chlorate in reclaimed water when using chlorine as a tertiary disinfection treatment. This study aimed at evaluating if chlorine-treated reclaimed water from a Municipal Wastewater Treatment Plant resulted in the accumulation of chlorate in commercially grown romaine lettuce. The risk of accumulation in the edible parts of the head was also examined by comparing the internal, middle, and external leaves as well as the roots. The results showed that the irrigation with chlorinated reclaimed water resulted in the accumulation of chlorate in fresh lettuce (0.34–0.56 mg kg −1 ), despite that the chlorate content in irrigation water was below the maximum residual level (MRL) allowed for potable water (0.25–0.49 vs. 0.70 mg L −1, respectively). The chlorate content gradually increased from the inner leaves (younger) (0.21 mg kg −1 ) to the outer leaves (oldest) (0.55 mg kg −1 ), and the roots (0.56 mg kg −1 ). This study shows that there was chlorate bioconcentration observed in fresh lettuce heads, although it did not exceed the current maximum residue levels for chlorate on leafy greens (0.7 mg kg −1 ) established in the amended Regulation (EC) No 396/2005 (SANTE/10684/2015 Rev. 9) recently adopted. However, the use of chlorate-free disinfectants as antimicrobial agents for the irrigation of edible crops with a low level antimicrobial residual to protect water in distribution systems is recommended to reduce the chlorate intake by consumers. Highlights: Chlorate content in irrigation water from reclaimed water was lower than the MRL allowed for potable water. Irrigation with reclaimed water led to a chlorate bio-concentration in lettuce heads. Chlorate content in commercial lettuce was 2–4 times higher than the proposed MRL for leafy vegetables. Chlorate content gradually decreased from the outer leaves to the inner leaves.